Burden of arrhythmia and silent ischemia in heart transplant patients with cardiac allograft vasculopathy. (1st October 2021) - Berg, Katrine; Bjerre, Kamillla Pernille; Clemmensen, Tor Skibsted; Løgstrup, Brian Bridal; Mølgaard, Henning; Poulsen, Steen Hvitfeldt; Eiskjær, Hans
Abstract: Background . The incidence of sudden cardiac death (SCD) following heart transplantation (HTx) accounts for approximately 10% of post-HTx deaths. Ischemia, brady- and tachy-arrhythmias caused by rejection and cardiac allograft vasculopathy (CAV) seem related to SCD. Hence, we aimed to investigate the relation between CAV, arrhythmias and silent ischemia in long-term HTx patients. Methods . 49 HTx patients were included. Patients were CAV classified in accordance with guidelines from the International Society of Heart and Lung Transplantation. Patients were divided into predefined CAV groups (CAV 0, CAV 1, CAV 2 + 3). Incidences of arrhythmia and silent ischemia were detected by 48-h electrocardiogram monitoring and analyzed blinded to CAV-status. Results . Median time since transplantation was 9 years [IQR 4–14]. We observed a higher incidence of non-sustained ventricular tachycardia (NSVT) in CAV 2 + 3 patients than CAV 0 and 1 patients ( p  = .01). Likewise, isolated premature ventricular complexes (PVC) ( p  = .01) and PQ-interval prolongation ( p  = .01) were more frequent in CAV 2 + 3 patients than CAV 0 and 1 patients. Silent ischemia was only observed among CAV 3 patients ( p  = .04). We saw no significant difference in the incidence of supraventricular tachycardia among CAV groups ( p  = .21). Likewise, no difference in the right bundle branch block was observed ( p  = .68). Conclusion . NSVT was associated with CAV status in long-term HTx patients. Patients with moderate to severe CAV showed higher incidences of PVCs and PQ-interval prolongation than patients with mild or no CAV. Silent ischemia was only seen in patients with severe CAV.